Synthesis and Characterization of P-PPD-Ph-Conjugated Flame Retardant - Sun, Junzhuo; Zhang, Daohai; Wei, Ke; Tan, Fang; He, Min; Bao, Dongmei; Qin, Shuhao (Frontiers in Chemistry, 2022)
The conjugated flame retardants have rarely been studied, a conjugate flame retardant 4, 4'-{1'', 4''-phenylene-bis[amino- (10'''-oxy10'''-hydro-9'''-hydrogen- 10'''λ5-phosphaphenanthrene-10''-yl)-methyl]}-diphenol (P-PPD-Ph) was synthesized and added into Polylactic acid(PLA) matrix. The P-PPD-Ph conjugated flame retardant structure was tested by FTIR, 1H and 31P NMR analysis. The thermal and rheological properties of PLA/P-PPD-PH conjugated flame retardant composites were investigated. The results showed that P-PPD-Ph conjugated flame retardant has a effect on PLA/P-PPD-PH conjugated flame retardant composites for promoting the formation of carbon layer, when the P-PPD-Ph conjugated flame retardant content was 15%, the residual carbon ratio for PLA/P-PPD-PH conjugated flame retardant composites increased by 4.2%.